Research on the Practical Significance of the Dual Functions of Painting Theory in Two-Dimensional Innovative Design of Intangible Cultural Heritage Cloud Collars - Li, Zhaole; Yang, Qianshui; Li, Xinyao (Education Insights, 2026)
Put forward by Li Shutong, the Dual Functions of Painting Theory marks the core theoretical origin of modern Chinese indigenous design aesthetic education. It clearly defines the dual values of fine art—'applied beauty' and 'noble beauty'—breaking the conventional mode of traditional art aesthetic education that prioritizes spiritual connotation over practical utility. Currently, the inheritance of the cloud collar, an item of intangible cultural heritage (ICH), faces multiple challenges, including homogeneous innovation, superficial cultural interpretation, and a disconnect between practical function and aesthetic appreciation. Innovative approaches limited to copying traditional patterns fail to meet the requirements of contemporary living inheritance. Centered on Li Shutong's theory and integrating his aesthetic education viewpoints, this paper explores the adaptive logic and practical approaches of the theory in the planar innovation of ICH cloud collars. This is examined from three perspectives: practical creation innovation, infiltration of spiritual aesthetics, and sublimation of personality-oriented aesthetic education. The research concludes that the Dual Functions of Painting Theory furnishes standardized theoretical support for the two-dimensional innovation of cloud collar heritage. It enables two-way empowerment: practical design facilitates modern industrial application while aesthetic inheritance preserves traditional culture. Ultimately, the theory effectively eliminates the shallow development bottleneck in the innovative transformation of traditional costume heritage, delivering an innovative paradigm for the modern conversion of Chinese traditional apparel ICH.